Lignin characterization by acetylation procedures - Cateto, C.A. (2011)
The amount of the total hydroxyl content of lignin is of great importance in the formulation of a lignin based polyurethane system since it allows the quantity of the polyisocyanate counterpart within the right stoichiometry. In this work, the reliability of an acetylation procedure, regarding the determination of total hydroxyl content of a commercial kraft lignin, was studied. Lignin was acetylated using acetic anhydride reagent in solution in pyridine and the recovered acetylated samples were analysed by FTIR using KBr pellets. The experimental variables investigated were: reaction time, reaction temperature, composition of the acetylation reagent, presence of a catalyst and drying process of the acetylated samples. Within this work, the obtained results indicate that acetylation was incomplete for all the studied conditions, resulting in an unreliable total hydroxyl determination and shows the limitation of this technique. This observation is in accordance with recent published works (see, for example, Gosselink et al., 2004) and could justify the lack of agreement among some published experimental results concerning interlaboratory analysis.